(untitled) (GEON Journal (Management, Organizations and Business), 2017)
This research analyzes the factors that influence mobility in the center and north of the city of Armenia from the viewpoint of governance. different factors of political, economic, social, cultural, infrastructural and administrative, in order to assess the management of public administration and policy analysis in infrastructure socio-economic development is studied, social welfare and region. The results presented are obtained from the first phase of research completed. The methodological design is part of an investigation of analytical and empirical cut mixed approach, which is made up of three stages: the first quantitative in nature through surveys Likert applied to a sample of private drivers; the second, qualitative court, where a sub-sample of public sector actors is investigated through interviews; and a third where a glut of data mediated grounded theory develops. Finally, correlation of variables is made, through multivariate analysis method. Consequently, a correlation is determined by three influential factors, such as: knowledge of public administration, ease of acquisition of financial credits for vehicles, and the absence of public policies to improve mobility. administrative and social - is a direct correlation between the influential political factors were also identified. In addition, a second correlation between administrative and cultural factors is given. These aspects produce inadequate policies to address the problem of mobility, which is to propose inputs that contribute to raise political and strategic direction of mobility.